AKTUALISASI KECERDASAN INTERPERSONAL PIMPINAN DALAM PENGEMBANGAN MUTU RUMAH TAHFIZH AHLUL QUR’AN PADANG - Putra, Fadli Padila; Prastowo, Andi; Rahmawati, Riska (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2024)
In order to help leaders develop the quality of the Ahlul Qur'an Tahfizh House, this study tries to ascertain how the dimensions of social sensitivity, social insight, and social communication have actually been implemented. This study used a qualitative descriptive research design and used observation, interviews and documentation as data collection methods. Data reduction, data presentation, and data verification are the stages of analysis used. The results of this study indicate that: first, there is an actualization or real embodiment of the social sensitivity dimension in the form of empathy, social sensitivity, showing respect and giving appreciation to ustadz/ustadzah and students of the Tahfizh Ahlul Qur'an House. Second, there is the actualization of the social insight dimension in the form of the ability to handle the problems faced. Third, there is the actualization of the social communication dimension in the form of the ability to establish communication with the residents of the Ahlul Qur'an Tahfizh House in order to achieve the goals of the institution. These forms of actualization are a way to be able to develop the quality of the Ahlul Qur'an Tahfizh House.